An integrated frame for designing conversations about futures. (February 2022) - Conway, Maree
Highlights: Conversations about futures must ensure that underpinning assumptions sare challenged in organisational futures processes. Four types of conversations, each holding assumptions about how possible futures are understood are identified. Assumptions shape the types and range of futures that emerge in organisations. Outlines a design frame for foresight/futures processes to integrate all assumptions. Abstract: A new Futures Conversations Framework (FCF) is proposed in this paper, one that draws on Integral Futures to integrate four types of conversations about futures – Self, Culture, Change and Futures – that each hold assumptions about how futures are understood and articulated in the present. The FCF is a design frame that seeks to ensure that any useful conversation about possible futures takes place in a space that surfaces and challenges these assumptions with the aim of expanding organisational discourses about futures and how those futures are used in the present. This paper is conceptual in nature and focuses on organisational futures and explores the nature and emphasis of each conversation before suggesting how an integrated framework can be used in practice to inform the design of foresight and futures processes to ensure as many assumptions about futures as is possible are identified in the present.